1996
DOI: 10.1007/bf01463656
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of estradiol receptor in paraffin sections of resting porcine uteri by microwave treatment. Immunostaining patterns obtained with different primary antibodies

Abstract: The unmasking of estradiol receptor in paraffin sections of Bouin's-fixed uterine tissue from ovariectomized gilts was attained with microwave treatment. Immunocytochemistry of the receptor was performed using a polyclonal or five monoclonal antibodies, two of which are commercially available, reacting with different domains of the protein and an amplified-peroxidase system for detection. With five of the antibodies, a predominance of nuclear staining was observed in cells of endometrial glands, while one mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…For the receptor isoforms, porcine uterus was used as a positive control. Tissue sections of 5 μ m were mounted onto Super Frost‐plus glass slides (Menzel Glaeser, Braunschweig, Germany) and mouse monoclonal primary antibodies raised against a peptide mapping at the carboxy terminus of the porcine ER α (clone HT277) (Sierralta and Thole 1996; Qualmann et al. 2000) and against the highly conserved carboxy terminus of the ER β 1 of human origin (clone PPG5/10; Serotec, Düsseldorf, Germany) were used for localization of ER α and ER β , respectively, while mouse monoclonal antibody against a conserved epitope within human P450 aromatase (cone SM1671P; Acris, Hiddenhausen, Germany) was used to detect P450 aromatase.…”
Section: Methodsmentioning
confidence: 99%
“…For the receptor isoforms, porcine uterus was used as a positive control. Tissue sections of 5 μ m were mounted onto Super Frost‐plus glass slides (Menzel Glaeser, Braunschweig, Germany) and mouse monoclonal primary antibodies raised against a peptide mapping at the carboxy terminus of the porcine ER α (clone HT277) (Sierralta and Thole 1996; Qualmann et al. 2000) and against the highly conserved carboxy terminus of the ER β 1 of human origin (clone PPG5/10; Serotec, Düsseldorf, Germany) were used for localization of ER α and ER β , respectively, while mouse monoclonal antibody against a conserved epitope within human P450 aromatase (cone SM1671P; Acris, Hiddenhausen, Germany) was used to detect P450 aromatase.…”
Section: Methodsmentioning
confidence: 99%
“…ERα cytoplasmic distribution has also been described in other tissues [50,51]. It was shown that different accessibility of the ER to the reagents depending upon the functional activity of the estradiol-controlled cells could interfere with subcellular immunolocalization of the receptor [50,52]. In agreement with this finding, ERα and ERβ were more frequently localized to the cytoplasm of resting uterine cells [51] and human breast cells [45].…”
Section: Discussionmentioning
confidence: 56%
“…The apparent discrepancy to reports that describe the absence of ESR1 expression in epithelial cells during early pregnancy may be the result of different antibodies being used. Subcellular staining patterns of ESR1 can depend on the primary antibody used for localization studies; for instance, a particular antibody can show a preference for cytoplasmic staining versus nuclear staining and vice versa (Schuler et al 2002 ;Sierralta and Thole 1996 ). It should be noted that during early pregnancy in the pig, luminal and glandular epithelial cells maintain ESR1 expression, albeit with immunoreactivity confi ned to nuclei and not the cytoplasm (Geisert et al 1993 ;Knapczyk-Stwora et al 2011 ).…”
Section: Spatial and Temporal Regulation Of Endometrial Receptors Formentioning
confidence: 97%